The essence of outsourcing and catering services in hotels and methods of their application - Bakhriddin Davlonov (THE INNOVATION ECONOMY, 2026)
This article presents scientifically based proposals and recommendations on the priority areas of scientific research in this area, such as outsourcing and types of outsourcing and catering services and their connection with the human factor, modern forms of organizing outsourcing and catering services in hotels, the market of outsourcing and catering services, composition and specific features, directions of development of outsourcing and catering services, innovative approaches and the use of digital technologies in organizing outsourcing and catering in hotels, etc